Learning Style Preferences in the Comprehension of Literary Texts - Abu, Abdul Ghani (2006)
The objective of the study was to identify learning styles preferred by learners in a higher learning institution in comprehending literary texts - short stories - in English. It also examined the relationship between several learner factors such as learners’ attitude and motivation in reading short stories and learners’ learning styles preferences. In addition, this study also examined the effects of specially designed reading lessons (based on Kolb’s learning model) on the learners’ ability to comprehend literary texts.